THE STUDY OF THE COMPLEX FORMATION OF THE COPPER(II) ION WITH SALICYLIC ACID BY MEANS OF THE EPR AND UV-VIS SPECTROSCOPY METHODS WITHIN WIDE RANGE OF AQUEOUS MEDIUM’S pH VALUES (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The complex formation of the copper(II) ion with salicylic acid by means of the EPR and UV-Vis spectroscopy methods has been studied under standard conditions within pH 4.0–10.2 values. It has been shown that in the pH 4.0–5.5 acidic media the I type complex is formed, in which the Cu2+ ion is connected with two salicylic acid ligands H2Sal and two water molecules, when in the pH 7.5–10 alkaline media the type II complex is formed, in which the Cu2+ ion is connected only with two salicylic acid anions Sal2–. By means of the EPR and UV-Vis spectroscopy methods it has been also estimated that the ligand field of the type I complexes is strengthener than that of the type I complexes.
Keywords: copper(II) ion, salicylic acid, complex formation